Ecological restoration in urban environments in New Zealand. (27th September 2016) - Clarkson, Bruce D.; Kirby, Catherine L.
Abstract : In the last two decades, the research and practice of restoration in New Zealand has extended into urban ecosystems, where it presents unique challenges and opportunities. This account reviews the history and current state of ecological restoration in urban environments in a country with one of the longest traditions of restoration in the world.